2000
DOI: 10.2754/avb200069040297
|View full text |Cite
|
Sign up to set email alerts
|

Total Antioxidant Capacity (TAC) Values and Their Correlation with Individual Antioxidants in Healthy Beagles

Abstract: The paper aims to establish a range for serum Total Antioxidant Capacity (TAC) and to determine the correlation between TAC and some individual antioxidants (vitamin A and E, lipid standardised vitamin E [Vit E/LS/], β-carotene, total bilirubin and albumin) in a uniform population of beagle dogs. Emphasis was directed on their general health status to establish a basis for future investigation of the role of TAC in diseases of dogs as species most frequently studied in veterinary medicine. The animal body poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…However, Rubio et al [36] recently published the results of full validation of an automated assay for the measurement of cupric reducing antioxidant capacity in the serum of dogs. Our results on TAC are in good agreement with the results of studies that employed the same or similar assay kit for the assessment of plasma or serum TAC in healthy dogs [7,26,37,38].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, Rubio et al [36] recently published the results of full validation of an automated assay for the measurement of cupric reducing antioxidant capacity in the serum of dogs. Our results on TAC are in good agreement with the results of studies that employed the same or similar assay kit for the assessment of plasma or serum TAC in healthy dogs [7,26,37,38].…”
Section: Discussionsupporting
confidence: 81%
“…By removing reactive oxygen species (ROS), intracellular antioxidant enzymes, SOD, GSH-Px, and catalase represent a primary antioxidant defense [6]. Data on the reference ranges of TAC [7], GSH-Px, and SOD [8] in healthy dogs are lacking, and there are no published accepted standard reference methods for their determination. Various measurement methods have been developed for the determination of TAC, GSH-Px and SOD; however, these methods differ greatly among studies, which led to discrepancies in the results [5,[9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In ruminant nutrition, this kind of diet, rich in essential fatty acids, has adverse effects like the increased conversion of polyunsaturated fatty acids, derived from essential fatty acids, to lipid peroxides (HUSVÉTH et al, 2000;CASTILLO et al, 2001b). But normally the body is protected by a wide range of antioxidant systems that neutralise harmful oxidants (NEMEC et al, 2000). Our results reveal that the increase in LOOH production is not parallel to an increase in TAS levels.…”
Section: Resultsmentioning
confidence: 53%
“…The latter are highly reactive and have been shown to interact with many biological components such as proteins, aminoacids, amines or DNA (CASTILLO et al, 2001a). On the other hand, the animal body has a variety of protective antioxidant substances that act as a harmoniously and finely tuned mechanism to neutralize harmful oxidants (MILLER et al, 1993;NEMEC et al, 2000). When the oxidant substances are not effectively and safely removed, oxidative stress may impair health in dairy cows both directly and indirectly (SIES, 1985;MILLER et al, 1993;DAVIES, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We compared our results in healthy dogs with GPX, CAT and SOD activities published for three healthy Beagles (Nakamura et al, 1999) and found significantly higher activities of all the enzymes in our dogs, probably due to differences in the methodologies used. A second study (Nemec et al, 2000) reported TAC values in serum of healthy, one to three year old Beagles. A second study (Nemec et al, 2000) reported TAC values in serum of healthy, one to three year old Beagles.…”
Section: Discussionmentioning
confidence: 99%